Design and robust control of a dual-loop valve-controlled cylinder system - Lijuan Zhao; Tiangu Wu (Results in Engineering)
To address the critical challenges of abrupt dynamic impacts and lumped disturbances arising from fault-induced loop switching, and to enhance control robustness and operational continuity in hydraulic support pushing systems under complex mining conditions, this paper proposes a novel fault-tolerant control strategy. The novelty of this work lies in the integration of a dual-loop redundant switching architecture with a Robust Sliding Mode Controller (RSMC) enhanced by an Extended Sliding Mode Observer (ESMO). The ESMO is designed to online estimate and actively compensate for the lumped disturbances, which encapsulate unmodeled dynamics, load variations, and severe transients from valve switching. A dynamic model incorporating the valve'S-type closing characteristic is established to facilitate the observer and controller design. The estimated disturbance is then utilized for feedforward compensation, significantly improving the system's tracking precision and stability. Experimental and simulation results demonstrate that, compared to a conventional Sliding Mode Controller (SMC), the proposed ESMO-RSMC strategy reduces the peak disturbance error by 60.4% and shortens the initial convergence time from 0.08 s to an immediate response within the error band. This research confirms that the integrated strategy effectively manages potential servo valve malfunctions, significantly suppresses switching disturbances, and enhances the system's fault tolerance and robustness, which is adequate for real-world applications.